Un modelo de formación basado en las competencias : hacia un nuevo paradigma en la enseñanza universitaria - Rosa María Rodríguez Izquierdo (Universidad de La Rioja, 2013)
Given the new reality of the European Higher Education Area (EHEA), professional titles and profiles, formation based on competences has become the main component of formation at the university. In this last decade, technological, economic and social transformations are placing professional demands on revising the content, means, methods and social forms of work. This article analyzes one of the most important challenges that universities have to confront in the coming years: to redefine their formative offer to provide a more fitting answer to society's and individuals' demands. We will explore a model of formation based on competences and the changes that this model im- plies for teaching staff and students. Reflections are placed within a framework of the innovation processes. Innovation is suggested as a collaborative solution.